The Assessment of sustainable poultry practices and technical efficiency of poultry egg farmers in Oyo State, Nigeria: Insights from a Cross-Sectional Survey of Poultry Farmers - Olatunji Hamzat; Kolawole Safiyu; Adewumi Ajibade; Daniel Olatidoye (Universitas Airlangga, 2026)
This study assessed sustainable poultry practices and the technical efficiency of poultry egg farmers in Oyo State, Nigeria. A sample of 276 farmers was selected using multistage sampling technique. A stochastic frontier analysis (SFA) based on the Cobb-Douglas production function was used to estimate efficiency levels and examine how sustainable poultry practices influence technical efficiency. Descriptive results showed that poultry production is largely male‑dominated (84.7%), and most farmers had tertiary education. The average age and farming experience were 45 years and 5.74 years respectively. Major sustainable poultry practices adopted (mean = 3.00) included protecting poultry houses from rain, sun, and wind; regular cleaning and disinfection; providing clean water daily; ensuring quality balanced feed; using feeders and drinkers that minimize wastage; following vaccination and deworming schedules; controlling flies and odors; storing manure away from water sources; involving women in farm management; and keeping proper financial records. The mean technical efficiency was 0.89, indicating that farmers operated close to the production frontier. In the inefficiency model, sustainable poultry practices had a significant negative coefficient, showing that higher adoption reduces technical inefficiency and improves efficiency. The study recommends that agricultural policy frameworks promote and incentivize sustainable poultry practices.